Keys to Play: Music as a Ludic Medium from Apollo to Nintendo - Moseley, Roger (University of California Press, 2016)
How do keyboards make music playable? Drawing on theories of media, systems, and cultural techniques, Keys to Play spans Greek myth and contemporary Japanese digital games to chart a genealogy of musical play and its animation via improvisation, performance, and recreation. As a paradigmatic digital interface, the keyboard forms a field of play on which the book's diverse objects of inquiry-from clavichords to PCs and eighteenth-century musical dice games to the latest rhythm-action titles-enter into analogical relations. Remapping the keyboard's topography by way of Mozart and Super Mario, who head an expansive cast of historical and virtual actors, Keys to Play invites readers to unlock ludic dimensions of music that are at once old and new.